Volumetric hyperthermia delivery using the ExAblate Body MR-guided focused ultrasound system - Kisoo Kim; Pragya Gupta; Kazim Narsinh; Chris J. Diederich; Eugene Ozhinsky (International Journal of Hyperthermia)
Objectives To investigate image-guided volumetric hyperthermia strategies using the ExAblate Body MR-guided focused ultrasound ablation system, involving mechanical transducer movement and sector-vortex beamforming.Materials and methods Acoustic and thermal simulations were performed to investigate volumetric hyperthermia using mechanical transducer movement combined with sector-vortex beamforming, specifically for the ExAblate Body transducer. The system control in the ExAblate Body system was modified to achieve fast transducer movement and MR thermometry-based hyperthermia control, mechanical transducer movements and electronic sector-vortex beamforming were combined to optimize hyperthermia delivery. The experimental validation was performed using a tissue-mimicking phantom.Results The developed simulation framework allowed for a parametric study with varying numbers of heating spots, sonication durations, and transducer movement times to evaluate the hyperthermia characteristics for mechanical transducer movement and sector-vortex beamforming. Hyperthermic patterns involving 2-4 sequential focal spots were analyzed. To demonstrate the feasibility of volumetric hyperthermia in the system, a tissue-mimicking phantom was sonicated with two distinct spots through mechanical transducer movement and sector-vortex beamforming. During hyperthermia, the average values of Tmax, T10, Tavg, T90, and Tmin over 200 s were measured within a circular ROI with a diameter of 10 pixels. These values were found to be 8.6, 7.9, 6.6, 5.2, and 4.5 °C, respectively, compared to the baseline temperature.Conclusions This study demonstrated the volumetric hyperthermia capabilities of the ExAblate Body system. The simulation framework developed in this study allowed for the evaluation of hyperthermia characteristics that could be implemented with the ExAblate MRgFUS system.